Long-term survival of a patient with gastric cancer with bone marrow metastasis receiving S-1 plus oxaliplatin beyond three years: a case report and literature review - Suto, Hirotaka; Inui, Yumiko; Okamura, Atsuo (Frontiers in Oncology, 2024)
Background: Bone marrow metastasis (BMM) of gastric cancer (GC), which is the most common cause of disseminated intravascular coagulation (DIC) among solid tumors, has a poor prognosis. Studies on prognostic improvement beyond one year in patients with GC with BMM are limited. This is the first report of a patient who survived over three years after 30 months of S-1 plus oxaliplatin (SOX) therapy for GC with BMM. Case Report: The patient was a 72-year-old woman who presented with anemia and high levels of alkaline phosphatase (ALP) and carbohydrate antigen 19-9 (CA19-9). Detailed examination led to the diagnosis with BMM of GC uncomplicated by DIC and the SOX regimen was initiated in November 2018. After six cycles, she was switched to S-1 monotherapy, and both ALP and CA19-9 levels reached normal by November 2019. However, computed tomography in April 2021 showed multiple bone metastases. Therefore, she was switched to paclitaxel-based therapy. In November 2021, the patient was further switched to nivolumab monotherapy, but she succumbed due to DIC in March 2022. Conclusion: GCs with BMM are prone to DIC, and the SOX regimen, which includes S-1 with efficacy against micrometastases, may constitute a safe and effective treatment modality.